2018
DOI: 10.1016/j.bpj.2018.01.028
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of DEG/ENaCs by Amphiphiles Suggests Sensitivity to Membrane Alterations

Abstract: The bile acid-sensitive ion channel is activated by amphiphilic substances such as bile acids or artificial detergents via membrane alterations; however, the mechanism of membrane sensitivity of the bile acid-sensitive ion channel is not known. It has also not been systematically investigated whether other members of the degenerin/epithelial Na channel (DEG/ENaC) gene family are affected by amphiphilic compounds. Here, we show that DEG/ENaCs ASIC1a, ASIC3, ENaC, and the purinergic receptor P2X2 are modulated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 61 publications
(91 reference statements)
5
16
0
Order By: Relevance
“…The authors proposed that the observed effects were mainly due to membrane alterations in the presence of tested surface-active substances. However, a clear correlation between the amphiphilic substance-mediated changes in membrane properties and alterations of P2X2 function was not observed (Schmidt et al, 2018). Thus, the observed effects may also be caused by specific interactions of membrane-active substances with the channel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors proposed that the observed effects were mainly due to membrane alterations in the presence of tested surface-active substances. However, a clear correlation between the amphiphilic substance-mediated changes in membrane properties and alterations of P2X2 function was not observed (Schmidt et al, 2018). Thus, the observed effects may also be caused by specific interactions of membrane-active substances with the channel.…”
Section: Discussionmentioning
confidence: 99%
“…Bile acids are membrane-active substances (Helenius and Simons, 1975) and therefore their incorporation into the plasma membrane may potentially influence P2X4 function by modulating the physical properties of the membrane. Recently, it has been reported that another purinergic receptor rP2X2 can be modulated by diverse amphiphilic substances (Schmidt et al, 2018). The authors proposed that the observed effects were mainly due to membrane alterations in the presence of tested surface-active substances.…”
Section: Discussionmentioning
confidence: 99%
“…What is the mechanism of inhibition of rat P2X2 by bile acids? A previous study has shown that P2X2 is sensitive to alteration of the plasma membrane induced by membraneactive substances [43]. and thus can affect the properties of the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…One possible mechanism of P2X2 inhibition might therefore involve modulation of the plasma membrane by bile acids, which then indirectly influences the activity of the P2X receptor. However, a modulation of the plasma membrane of Xenopus oocytes by bile acids that has an impact on the activity of Deg/ENaC channels like BASIC probably requires higher concentrations [43]. Thus, either P2X2 is more sensitive to membrane alterations or bile acids directly bind to P2X2, either in the ECD or in the TMDs.…”
Section: Discussionmentioning
confidence: 99%
“…A detailed literature analysis of the effects of the tested alkaloids on ion channels in cell membranes has revealed the possibility of their lipid-mediated action (Lundbaek et al, 2005;Søgaard et al, 2006;Ingólfsson et al, 2014;Schmidt et al, 2018). It was found that a decrease in membrane stiffness in the presence of capsaicin is responsible for modulating the activity of voltage-dependent sodium channels (Lundbaek et al, 2005), GABA receptors (Søgaard et al, 2006), and degenerin/epithelial sodium channels such as ASIC1a, ASIC3, ENaC, and P2X2 (Schmidt et al, 2018). Ingólfsson et al (2014) showed similar effects for mechano-sensitive channels of large conductance (MscL), the voltage-dependent potassium channel Kv2.1, and neuronal voltage-dependent sodium channels (NaV).…”
Section: Reconstituted Ion Channelsmentioning
confidence: 99%